Immunotherapy in head and neck squamous cell carcinoma and rare head and neck malignancies - Stefano Cavalieri; Daria Maria Filippini; Arianna Ottini; Cristiana Bergamini; Carlo Resteghini; Elena Colombo; Roberta Lombardo; Imperia Nuzzolese; Salvatore Alfieri; Lisa Licitra; Laura D. Locati (Open Exploration Publishing Inc., 2021)
The dismal prognosis of recurrent/metastatic (R/M) head and neck squamous cell carcinoma (HNSCC) prompted recent advances in the field of therapeutic approaches beyond cytotoxic cancer therapy. In recent years, the deeper and increasing knowledge on the genomic landscape and the upcoming new data on immunotherapy enacted by HNSCCs have led to successful therapeutic targeting of the immune system. Immune checkpoint inhibitors (ICIs) have changed state of the art in R/M patients and could have a potential role even in early disease. The purpose of this work is to summarize the role of immunotherapy for R/M HNSCC in clinical practice, with insights about future perspectives. Updated immunotherapy results in other R/M head and neck cancers such as thyroid, salivary glands, nasopharynx, sinonasal cancers, and nuclear protein in testis (NUT) are presented.